Assessing adaptation of the psychometric properties of the General Health Questionnaire (GHQ-12) using the Rasch Measurement Model among Indian teenagers - Ali, Syed Faraz; Khan, Aqeel; Abdul Latif, Adibah Binti; Pathath, Abdul Wahab; Shabnam, Shabnam; Asif, Mohammad; Rosman, Arieff Salleh (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2023)
The General Health Questionnaire (GHQ-12) is widely accepted as an instrument used to examine diagnosable psychiatric disorders. It is also routinely used as a measure of psychological morbidity. This study aimed to assess and establish the psychometric properties of the GHQ-12 among Indian teenagers. The tool was administered to 212 adolescents aged from 12 to 18 years. Following two-stage cluster sampling, the data were collected from Aligarh district, India. Fleiss Kappa analysis was used to determine test reliability and showed an overall value of 0.94, based on the rater agreement for the instrument. Furthermore, the Rasch measurement model was used, with values of 0.79 and 0.83 for person and item reliability, respectively. Moreover, the value of unidimensionality was found to be 37.9%. Additionally, item fit statistics and item analysis were conducted for the instrument. Based on the preliminary data and findings, the study provides primary evidence for the reliability and validity of GHQ-12. Hence, the questionnaire can lead to more multi-site studies in India.